Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2014
DOI: 10.1515/jpem-2013-0314
|View full text |Cite
|
Sign up to set email alerts
|

A truncating DUOX2 mutation (R434X) causes severe congenital hypothyroidism

Abstract: Mutations in DUOX2 have been reported to cause congenital hypothyroidism (CH), and our aim in this study was to determine the genetic basis of CH in two affected individuals coming from a consanguineous family. Because CH is usually inherited in autosomal recessive manner in consanguineous/multicase families, we adopted a two-stage strategy of genetic linkage studies and targeted sequencing of the candidate genes. First, we investigated the potential genetic linkage of the family to any known CH locus using mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 6 publications
0
17
0
Order By: Relevance
“…In contrast, a previous report of Turkish patients with homozygous p.R434X showed mental retardation due to delayed diagnosis at 6 months of age (26). Therefore, early diagnosis by neonatal screening programs and early treatment are important for patients with DUOX2 defects, even for transient CH.…”
Section: Discussionmentioning
confidence: 74%
See 2 more Smart Citations
“…In contrast, a previous report of Turkish patients with homozygous p.R434X showed mental retardation due to delayed diagnosis at 6 months of age (26). Therefore, early diagnosis by neonatal screening programs and early treatment are important for patients with DUOX2 defects, even for transient CH.…”
Section: Discussionmentioning
confidence: 74%
“…Other reports have shown that biallelic DUOX2 mutations cause mild to moderate CH (13,14,15,16,19,22,30). Recently, some studies have shown that DUOX2 defects are the predominant cause of CH associated with dyshormonogenesis (13,14,15,16,25,26).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Further comprehensive functional assessments of the detected mutation will reveal its exact mechanism in the pathogenesis of CH. The R434X mutation in the DUOXA2 was detected by a two-stage strategy of genetic linkage studies and targeted sequencing of the candidate genes, suggesting a new testing strategy which uses next-generation sequencing in CH cases (14). …”
Section: Discussionmentioning
confidence: 99%
“…To investigate genetic background of CH, we developed a two-tier strategy combining genetic linkage studies and full sequencing of candidate genes in familial cases and identified several mutations to date in different CH genes. [16][17][18][19][20][21][22][23][24][25][26] In the current study we aimed to determine genetic cause of CH in a consanguineous family with three affected siblings. Here we report a homozygous duplication (c.1184_1187dup4) in the TPO gene detected in all cases and associated clinical phenotypes.…”
Section: Introductionmentioning
confidence: 99%